An improved technique for oesophagojejunal anastomosis using the EEA Premium stapling gun. - Brough, W. (Royal College of Surgeons of England, 1989)
Using the new Premium Curved EEA stapling device we describe a modified technique for performing a safe oesophagojejunal anastomosis.